2017
DOI: 10.3389/fendo.2017.00136
|View full text |Cite
|
Sign up to set email alerts
|

Desynchronization of Circadian Clocks in Cancer: A Metabolic and Epigenetic Connection

Abstract: Circadian clocks are innate oscillators that drive daily rhythms in metabolism, physiology, and behavior. 24-h rhythms in gene expression, driven by core clock transcription factors, reflect the epigenetic state of the cell, which in turn is dictated by the metabolic environment. Cancer cells alter their metabolic state and gene expression and therefore are likely to tweak circadian clock function in their favor. Over the past decade, we have witnessed an extraordinary increase in systems-level studies that su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 95 publications
(98 reference statements)
1
16
0
Order By: Relevance
“…The amplitude of rhythmic expression of clock genes was decreased by MC-LR. Similar phenotypes have been observed in various pathophysiological settings, such as aging, obesity, and cancer [ 15 17 ], implicating the impairments of inner microenvironment homeostasis within cells. Our findings support this notion and provide evidence that MC-LR causes cellular toxicity by suppressing the robustness of the circadian clock.…”
Section: Discussionsupporting
confidence: 68%
“…The amplitude of rhythmic expression of clock genes was decreased by MC-LR. Similar phenotypes have been observed in various pathophysiological settings, such as aging, obesity, and cancer [ 15 17 ], implicating the impairments of inner microenvironment homeostasis within cells. Our findings support this notion and provide evidence that MC-LR causes cellular toxicity by suppressing the robustness of the circadian clock.…”
Section: Discussionsupporting
confidence: 68%
“…Based on these, clock genes have received increasing interest due to their key role in regulating the body homeostasis [ 4 , 6 , 8 , 9 ]. Interestingly, chronodisruption, i.e., loss of internal coherence among the biological clocks, has been linked to the development of cancer [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ], metabolic dysfunctions, and psychiatric disorders [ 4 , 5 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the landscape of melanoma treatment has significantly changed with the introduction of newer drugs that target BRAF, and its downstream molecule MEK, as well as antibodies that block immune checkpoints such as CTLA-4, PD-1 and its ligand (PD-L1) [ 32 , 33 , 34 , 35 ]. In addition to the classic genes related to development and progression of melanoma, as mentioned above clock genes are known to be frequently altered in several types of cancer [ 14 , 15 , 17 , 18 ]. Understanding how clock genes are altered in melanoma has become an attractive field of study.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst these processes are DNA damage repair, metabolism, and cell cycle ( Blakeman et al, 2016 ). The circadian clocks act as oscillators to drive 24-h rhythms in gene expression and protein function, and these rhythms help the organism maintain a homeostatic relationship with the environment ( Padmanabhan and Billaud, 2017 ). Disruption of circadian rhythms has been associated with various forms of cancer in humans, and it has been shown that a disordered circadian clock, whether genetically or due to environmental signals (e.g., changes of dark/light exposure) accelerates tumor progression ( Savvidis and Koutsilieris, 2012 ; Hadadi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%